The Impact of Excessive Gadget Usage Intensity on Student Social Interactions - Ritonga, Dandi Fhadillah; Wirtati, Ira (International Journal of Multidisciplinary Research of Higher Education, 2025)
The development of technology, especially gadgets, has changed the pattern of social interaction among adolescents, especially school students. The phenomenon of gadget dependence is increasing, which can reduce the intensity of direct interaction and face-to-face communication skills. This study aims to examine the impact of gadget use on students' social interactions. This research uses a qualitative method with a case study approach. This study involved students as research subjects. Data were collected through observation and in-depth interviews. The collected data were then analyzed to identify the impact of gadget use. The results showed that excessive gadget use can reduce social interaction with family and friends, social isolation, and decreased face-to-face communication skills. As an effort to overcome this, the school supervises the use of gadgets, educates the use of gadgets wisely by teachers, and some students try to manage gadget use by participating in social and sports activities.  The study emphasizes the importance of managing gadget use wisely and balancing digital activities with face-to-face social interactions.